Quantification of acidity and total soluble solids in guavas by near infrared hyperspectral imaging - Klinbumrung, Nutsinee; Teerachaichayut, Sontisuk (My University, 2018)
In order to provide premium quality for marketing of guavas the titratable acidity (TA) and total soluble solids (TSS) levels should be determined. A reflectance near infrared hyperspectral imaging (NIR-HSI) unit in the wavelength range of 936-1696 nm, which is a nondestructive technique, was tested for use in predicting TA and TSS. Samples of 100 guavas were scanned by NIR-HIS as a group for calibration (N=67) and as a group for prediction (N=33). The average spectra from the region of interest (ROI) of samples were used to establish the calibration models for TA and TSS by using partial least squares regression (PLSR) to establish calibration models. The calibration model for TA gave a coefficient of determination (R2) of 0.972 and the root mean square error of prediction (RMSEP) of 0.010% and for TSS the R2 was 0.801 and the RMSEP was 0.437°Bx. The accuracies of these results indicate that NIR-HSI has potential for use in measuring TA and TSS of guavas.
Keywords: calibration; model and nondestructive; near infrared; prediction